Spectroscopic markers for uranium(vi) phosphates: a vibronic study1. Issue 87 (20th September 2015) - Faulques, E.; Kalashnyk, N.; Massuyeau, F.; Perry, D. L.
<x xml:space="preserve">Abstract</x> Uranyl phosphate minerals are studied by optical and vibrational spectroscopy which provide robust markers to discriminate among environmentally hazardous uranium phases.